Teaching the Biography of Paruyr Sevak by Interactive Methods - Vardanyan, Arsen (Bulletin of Yerevan University B: Philology, 2025)
Studying the biography of each writer is an important key to a more comprehensive understanding of his work, understanding the connection between the period in which he lived and his work. Student-centered learning has gained special importance in the modern education system. No matter how important the role of the teacher was, the latter ceased to be the only source of knowledge. Therefore, a contemporary teacher should be able to combine traditional and modern teaching methods so that the lesson serves its purpose, which consists not only in the transfer of knowledge but also in the formation of abilities, a system of values, and a sense of peace. The first understanding of the writer begins with recognizing his character and activity. In the general education program, this is best achieved by teaching biographies of authors the ability to combine facts, draw conclusions, make creative work. The topic is relevant, as the teaching of biography is also given a lot of attention in the new educational standards so that interactive teaching methods can contribute to an interesting and effective presentation of the topic.We conducted research, collected, analyzed, and compared materials and concluded. During the teaching, we tested almost all the presented methods.
Keywords: Paruyr Sevak; biography; teaching; method; student; education; abilities